Outcome of allo simple limbal epithelial transplantation (alloSLET) in the early stage of ocular chemical injury. Issue 6 (8th October 2016) - Iyer, Geetha; Srinivasan, Bhaskar; Agarwal, Shweta; Tarigopula, Anil
Abstract : Purpose: To analyse the outcome of allo simple limbal epithelial transplantation (alloSLET) in eyes in the early stage following ocular chemical injury to achieve rapid epithelialisation. Patients and methods: Records of 18 eyes of 17 patients who underwent alloSLET between April 2013 and Jan 2016 were analysed retrospectively. Patients with grade 4 or worse Dua's classification for chemical injury, who presented within a month of the injury or with a non-healing epithelial defect since the injury despite earlier medical or surgical interventions, were included in the study. The time to epithelialisation was the primary outcome measure and the best corrected visual acuity, the clinically assessed epithelial phenotype and symblepharon formation were the secondary outcome measures. Results: The mean time to epithelialisation was noted to be 22.5±9.14 days. A best corrected visual acuity of better than 20/120 was achieved in 13 eyes in a mean duration of 33.06+10.73 days following alloSLET. Corneal phenotype with complete epithelialisation was achieved in the immediate postoperative period in 17 of the 18 eyes (94.11%). Seven eyes had a gradual failure of the allograft and 5 eyes underwent subsequent limbal autograft. Symblepharon formation involving one to two quadrants was noted in 3 eyes (16.7%). Conclusions: AlloSLET seems to be a useful technique to achieve rapid epithelialisation in severe chemical injuries thereby preventing the adverse effects of delayed epithelial healing. Visual rehabilitative procedures in the chronic phase of chemical injury, in most instances following an alloSLET in the acute stage, did not require keratoplasty, either lamellar or penetrating.